Species Diversity and Biological Vulnerability of Sharks in Indonesia’s Fisheries Management Area 573 - Roy Pereira; Ayu Adhita Damayanti; Soraya Gigentika (Jurnal Biologi Tropis, 2026)
The Tanjung Luar Fishing Port (PPTL) in East Lombok is one of Indonesia’s major shark-landing centers operating within Fisheries Management Area (WPP) 573 of the Indian Ocean. Intensive fishing activities carried out for commercial purposes have exerted significant pressure on shark populations in the region. This research aims to analyze species composition, conservation status, size distribution, and sex ratio of sharks landed at Tanjung Luar Fishing Port as a basis for developing sustainable shark fisheries management strategies. Data collection was conducted through direct observation of fishermen’s catches from March to June 2025. The results showed that a total of 2,002 individual sharks were identified, consisting of 33 species. The most dominant species was the silky shark (Carcharhinus falciformis), accounting for 46.6% of the total catch, followed by the tiger shark (Galeocerdo cuvier) (18.3%), the scalloped hammerhead (Sphyrna lewini) (6.6%), and Carcharhinus limbatus (5.7%). Based on the IUCN Red List (2023), the catch included 2 species classified as Critically Endangered (CR), 7 Endangered (EN), and 10 Vulnerable (VU), with 22 species listed in CITES Appendix II. The landed sharks were predominantly adults and subadults with total lengths ranging from 120–280 cm. The sex ratio revealed a significant imbalance, with approximately 3.3 females for every male. These findings indicate high exploitation pressure on shark populations, particularly on mature females, highlighting the need for adaptive and sustainable management strategies for shark fisheries.